The boy [videorecording (DVD)] - Bell, William Brent; Cohan, Lauren, 1982-; Evans, Rupert (Universal Pictures Home Entertainment, 2016)
Greta is a young American woman who takes a job as a nanny in a remote English village, only to discover that the family's eight-year-old is a life-sized doll that the parents care for just like a real boy, as a way to cope with the death of their actual son twenty years prior. After violating a list of strict rules, a series of disturbing and inexplicable events bring Greta's worst nightmare to life, leading her to believe that the doll is actually alive.